Burden of Buruli ulcer: how affected households in a Ghanaian district cope - Adamba, C.; Owusu, A. (African Study Monographs, 2011)
Buruli Ulcer (BU) is economically burdensome and socially stigmatising. We examined the burden of BU and the strategies commonly adopted by households in a Ghanaian district to cope with it. Respondents for the study were conveniently sampled using data from a BU unit within the District Health Centre. Adult BU patients and caretakers of minor patients (aged less than 15) who had reported for care within the past year were interviewed. A semi-structured questionnaire was used for the interviews. The staff in-charge of an international NGO with services to BU patients in the district was also interviewed. The disease was associated with poor rural households with mean annual incomes of the equivalent of USD490.70 or less. Other costs and stigma associated with the disease posed a great burden on the already poor households we studied. Households adopt coping strategies, including sale of assets, reduction in farm sizes, and avoiding people, all of which are potentially risky for future sustainability.
Keywords: Buruli ulcer; Coping strategies; Stigma; Poverty; Ghana